POU domain transcription factor BRN2 is crucial for expression of ASCL1, ND1 and neuroendocrine marker molecules and cell growth in small cell lung cancer. (26th March 2013) - Ishii, Jun; Sato, Hanako; Sakaeda, Masashi; Shishido‐Hara, Yukiko; Hiramatsu, Chie; Kamma, Hiroshi; Shimoyamada, Hiroaki; Fujiwara, Masachika; Endo, Tetsuya; Aoki, Ichiro; Yazawa, Takuya
<x xml:space="preserve">Abstract</x> BRN2 is a developmental neural cell‐specific POU domain transcription factor and is crucial for cell lineage determination. We investigated the importance of BRN2 in the expression of the lineage‐specific transcription factors (achaete‐scute homolog‐like 1 (ASCL1) and NeuroD1 (ND1)) and neural/neuroendocrine marker molecules (neural cell adhesion molecule 1 (NCAM1), synaptophysin (SYP) and chromogranin A (CHGA)) in small cell lung cancer (SCLC) using cultured lung cancer cells. All examined SCLC cell lines expressed BRN2, as well as ASCL1, ND1, NCAM1, SYP and CHGA. The expression levels of ASCL1, ND1, NCAM1, SYP and CHGA considerably decreased when BRN2 was knocked down in SCLC cells, and the addition of a BRN2 transgene into non‐SCLC (NSCLC) cells induced the expression of ASCL1, ND1, NCAM1, SYP and CHGA. However, the BRN2 gene was not activated by the forced expression of ASCL1 or ND1 in NSCLC cells. The knockdown of BRN2 caused significant growth retardation with decrease of S to G2 phase population and mitotic cell rates and unaltered Ki‐67‐labeled or apoptotic cell rates in SCLC cells, indicating increase of G1 phase population. These findings suggest that BRN2 is a higher level regulator than ASCL1 and ND1 and BRN2 might be involved in aggressiveness of SCLC.